MOLECULAR AND BIOCHEMICAL CHARACTERIZATION OF ECHINOCOCCUS SPP. IN HYDATID CYST FLUID COLLECTED FROM HUMAN AND LIVESTOCK IN NORTHERN KHYBER PAKHTUNKHWA AND GILGIT BALTISTAN - M. Abdullah; I. Ali; K. S. Haleem; A. U. Rehman; S. Qayyum; Z. Niaz; S. Ahmed; I. Khan; M. N. K. Khattak; N. Sultana; I. Tauseef3 (Journal of Animal and Plant Sciences, 2021)
The Echinoccocus spp. infection results in cystic or alveolar echinococcosis causing billions of dollars loss to the international economy in respect of expensive medical treatments, permanent loss of entire or part of organ, and a substantial decrease in livestock productivity. Therefore, the study was designed with objectives to know existence of the species, their genotypes and biochemical profile of hydatid cyst fluids of Echinococci in the samples collected from northern Khyber Pakhtunkhwa and Gilgit Baltistan. Cyst samples (n = 46) were collected from two different sources i.e. livestock and human (n=34 and n=12, respectively). PCR-RFLP based analysis was used to investigate the mitochondrial gene (rrnL, large subunit of ribosomal RNA) based species detection and genotyping. Biochemical assay of all hydatid cyst fluid was performed to analyze the concentration of various parameters i.e. uric acid, glucose and triglyceride etc. One-way ANOVA followed by Tukey’s post-hoc test was also performed to determine the statistically significant differences among the biochemical parameters. Among all collected cysts, 56.5% (n=26) were positive for Echinococcus granulosus while 43.4% (n=20) were detected as Echinococcus multilocularis. Genotyping of the positive E. granulosus revealed the highest frequency (>90%) of G1–3 genotype while G6 genotype was found at low level (<10%). In case of human, all samples were positive for G1–3 genotype. Biochemical analysis of cyst fluids showed a significant (P ≤ 0.05) interspecies variation in all tested parameters. In conclusion, E. granulosus and E. multilocularis are found frequently in northern KP and Gilgit Baltistan. Further, E. granulosus sensu stricto (G1-3) and G6 genotypes are responsible for infections in both human and animals. A comprehensive surveillance program in whole northern Pakistan is needed for effective prevention/control of Echinococcus species.
Keywords: Cyst; Echinococcus; Human; Livestock; Genotypes of E. granulosus